Effects of FecB Mutation on Estrus, Ovulation, and Endocrine Characteristics in Small Tail Han Sheep - Wang, Xiangyu; Guo, Xiaofei; He, Xiaoyun; Liu, Qiuyue; Di, Ran; Hu, Wenping; Cao, Xiaohan; Zhang, Xiaosheng; Zhang, Jinlong; Chu, Mingxing (Frontiers in Veterinary Science, 2021)
FecB gene has a mutation that was found to increase the ovulation rate and litter size in Booroola Merino sheep. This mutation is also associated with the fecundity of Small Tail Han (STH) sheep, an important maternal breed used to produce hybrid offspring for mutton production in China. Previous research showed that the FecB gene affects reproduction in STH sheep, based on litter size records. However, the effects of this gene on estrus, ovulation, and endocrine characteristics in these sheep remain unclear. Here, we analyzed the above traits and compared them among the three FecB genotypes of STH ewes using estrus synchronization. Overall, 53 pluriparous ewes were selected from among 890 STH ewes and subjected to FecB genotyping for experiments to characterize estrous and ovulation rates. FecB heterozygous (+B) ewes presented an earlier onset of estrus (42.9 ± 2.2 h) and a shorter estrous cycle (17.2 ± 0.2 d) (P  0.05). The ovulation rates increased with increasing copy number of the B allele (P  0.01). Ovulation time showed no significant differences among the three FecB genotypes. The serum concentrations of FSH, LH, E2, and P4 were measured in 19 ewes. Serum concentrations of E2 and FSH dramatically varied around the time of behavioral estrus. In FecB mutant homozygous (BB) ewes, E2 concentration had two peaks, which were higher (P  0.05) than those of wild (++) genotypes. FSH concentration of BB ewes was higher (P 0.05) than that of the ++ ewes just after estrus. The expression of the estrogen receptor 1 gene in the +B genotype was higher than in the other genotypes. Based on the data for the reproductive performance of STH ewes with different FecB genotypes, our study suggests that the follicles development in ewes with the B allele is dependent on the response to FSH regulated by E2 in the early stage. +B ewes, exhibiting moderate ovulation and litter size, and a shorter estrous cycle, can be highly recommended in sheep crossbreeding systems for commercial mutton production. Moreover, this study provides useful information to better conserve and use the genetic resources of STH sheep.